ANALISIS INFORMASI KEUANGAN KOPERASI SYARIAH NURI (KSN) JAWA TIMUR SEBAGAI ALAT PENGAMBILAN KEPUTUSAN INVESTASI - Putri, Devi Lestari Pramita; Maulana, Wahyu (School of Accountancy, University of Agung Podomoro, 2019)
Nowadays, economic conditions in Indonesia are unstable, with the result that it is needed to look for the information from certain or credible sources. Especially in financial information because of that, it is very influential to those who play an important role in policymakers. Besides, the precise financial information is also needed by the investors and creditors who are used as a basis for consideration to make profitable investments or vice versa. The objective of this study is to find out the financial information as an investment decision-making tool and to find out the level of health of cooperatives in the financial sector as financial information to investors and creditors. Then, the object of this study is Koperasi Syariah Nuri in East Java. This study employed descriptive quantitative research. The sampling technique is purposive sampling. The data sample used is in the form of financial statements from 2015 to 2017. Based on the data analysis, the results show us that: capital ratio in healthy criteria, cash ratio in liquid criteria, ROA insufficient criteria, ROE insufficient criteria, Fewer criteria generated by the service operational independence ratio.